Stock Liquidity and Cash Holdings: Evidence from Malaysia - Shiang Shen Kwan; Roy W. L. Khong; Woan Ting Hung (Asian Academy of Management Journal of Accounting and Finance, 2023)
The level of cash held by listed companies has raised academic interest. In particular, many studies have been conducted to understand the reason why companies hold so much cash. Previous studies on the determinants of cash holdings have focused on firm-specific characteristics. More recently, researchers have found that stock liquidity played an important role in explaining the cash holding behaviour. This study examines the effect of stock liquidity on cash holdings among listed companies in Malaysia. The findings indicate that stock liquidity has a positive impact on cash holdings. This suggests that companies have a higher propensity to hold cash to repurchase its own stocks, which resulted in higher stock liquidity.